DEVELOPMENT OF COGNITIVE AND PSYCHOMOTOR TEST INSTRUMENTS ON ENGINE COOLING SYSTEM MATERIAL USING A SIMULATOR (ATIKANOTO: Journal of Automotive Engineering Education, 2025)
This study aims to develop cognitive and psychomotor test instruments for the maintenance and repair of engine cooling systems using a self-made simulator. The research method employed the 4D development model (Define, Design, Develop, Disseminate). The cognitive instrument was designed in the form of multiple-choice questions to measure students’ understanding of the working principles, functions, components, and operation of the cooling system. The psychomotor instrument was developed based on actual work stages in performing maintenance and repair of engine cooling systems using an Arduino-based simulator. The research involved ten validators consisting of certified automotive technicians, practitioner lecturers, and gasoline engine technology lecturers. Validation was conducted to assess the feasibility of the instruments in terms of content, construct, and reliability. The validation results for the cognitive instrument showed a Content Validity Index (CVI) of 0.983, indicating that all test items were suitable for use. The psychomotor instrument was also declared feasible based on the content validation results. In conclusion, the developed cognitive and psychomotor test instruments meet the criteria of validity and reliability for use in learning evaluation of engine cooling system maintenance and repair using a simulator. Penelitian ini bertujuan mengembangkan instrumen tes kognitif dan psikomotor pada materi perawatan dan perbaikan sistem pendinginan engine berbasis simulator buatan sendiri. Metode penelitian menggunakan model pengembangan 4D (Define, Design, Develop, Disseminate). Instrumen kognitif disusun dalam bentuk soal pilihan ganda untuk mengukur pemahaman mahasiswa terkait prinsip kerja, fungsi, komponen, dan cara kerja sistem pendinginan. Instrumen psikomotor disusun berdasarkan tahapan kerja nyata dalam perawatan dan perbaikan sistem pendinginan engine menggunakan simulator berbasis Arduino. Subjek penelitian melibatkan sepuluh validator yang terdiri atas teknisi otomotif bersertifikasi, dosen praktisi, dan dosen teknologi motor bensin. Validasi dilakukan untuk menguji kelayakan instrumen meliputi aspek isi, konstruk, dan reliabilitas. Hasil validasi instrumen kognitif menunjukkan nilai Content Validity Index (CVI) sebesar 0,983 yang menandakan seluruh butir soal layak digunakan. Instrumen psikomotor juga dinyatakan layak berdasarkan hasil validasi isi. Kesimpulannya, instrumen tes kognitif dan psikomotor yang dikembangkan memenuhi kriteria valid dan reliabel untuk digunakan dalam evaluasi pembelajaran pada materi perawatan dan perbaikan sistem pendinginan engine berbasis simulator.